Struma ovarii – a dermoid and serous form of ovarian cyst - Dobrosława Sikora-Szczęśniak; Wacław Sikora (Studia Medyczne, 2013)
Struma ovarii belongs to the class of monodermal and highly specialized teratomas. These tumors are detected mainly among mature teratomas, accounting for up to 3% of all ovarian teratomas. Besides dermoid cysts, thyroid tissue is also found in serous and mucous cysts within the ovary. The aim of the research was to analysis of the incidence of struma ovarii – a rare type of tumor – among dermoid and serous ovarian cysts. Medical documentation of female patients subjected to surgery in the Department of Gynecology and Obstetrics, Independent Public Health Care Institution in Lipsko over a period of 17 years was reviewed for cases of struma ovarii. Struma ovarii was detected in 4 out of 103 operated females with dermoid and serous cysts. Thyroid tissue and serous cyst with a double-twisted pedicle were detected in a 22-year-old patient in the 10th week of gestation within the left ovary. In three cases of patients aged 42, 46, and 51, thyroid tissue encapsulated in dermoid cells was also located on the left side. All diagnoses were made on the basis of histopathological assessments. In a 17-year observation period, gestational struma ovarii was identified in one out of 17,751 patients whose pregnancies led to delivery. This accounts for 0.0068% of pregnancies ending with delivery. Struma ovarii was detected in one half of the patients in whom dermoid cells were detected bilaterally.